Key quality factors for Chinese herbal medicines entering the EU market - Mei Wang; Pei-Fen Yao; Peng-Yue Sun; Wen Liang; Xiao-Jia Chen (BMC, 2022)
Abstract Chinese herbal medicines (CHMs) have unique advantages in the prevention and treatment of diseases, which are widely recognized in the world. More and more CHMs are becoming increasingly popular in the international markets. However, the quality control of CHMs is a significant issue for their acceptance and recognition in the international market. This review mainly focuses on the quality requirements for CHMs to enter the European Union (EU) market. Both Chinese and European regulations and quality controls are compared. Firstly, the EU medicinal regulatory system and relevant regulations were reviewed. Secondly, the key factors of the quality control of CHMs, including Chinese herbal drugs, extracts and products were compared with those of European herbal medicines in the EU market. Subsequently, three main registration routes for herbal medicinal products including Chinese herbal medicinal products entering the EU were introduced. Furthermore, the legal status of traditional Chinese medicine granules in the EU was also discussed. Through the comparison of the key quality factors for CHMs in China and the EU, the similarities and differences in terms of quality requirements and regulations are addressed, which provides a reference for the development of CHMs into the EU market.